Sarı Saltuk Sanctuary In Bahçe Village Of Koyulhisar District In Sivas - Dinç, Abdulkerim (Journal of Alevism-Bektashism Studies, 2017)
The sanctuary tombs of Sarı Saltuk increase day by day and this shows the importance of his personality as a Saint. The newly registered tomb in Sivas, among his other sanctuary tombs around Anatolia and the Balkans, is in Bahçe village of Koyulhisar district in Sivas. The tomb is on a hill called Sarı Saltuk. The villagers claim that there are other infra-structures around the tomb. The villagers believe that he is a Saint, a Hero who is sent here by Ahmed Yesevî for Islamization of Anatolia. They also believe that he is in the same rank before Pir Sultan and Hacı Bektas-ı Velî. Around the sanctuary, there are Sultan Baba and Erdem Baba Sanctuaries. This study examines the oral stories and praying practices in Sarı Saltuk Sanctuary in Sivas.
Keywords: Keyword